Community Health Agents: health promotion skills for adolescents - Rosely Leyliane dos Santos; Maria Socorro de Araújo Dias; Antônio Germane Alves Pinto; Edilma Gomes Rocha Cavalcante; Maria de Fátima Antero Sousa Machado (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to identify the domains developed by Community Health Agents in health promotion skill towards adolescents. Method: qualitative study conducted with 16 Community Health Agents, based on the methodological framework of professional skills. Results: two categories and nine domains of health promotion skills emerged: Knowledge (Concept; Health determinants and conditioning factors; Main population health problems and coping; Intersectoriality); and Skill (Identifying the relationship between health problems; Conducting educational activities; Organizing discussion groups; Proposing and implementing intersectoral actions and establishing articulation with social facilities; Supporting social literacy actions). Final consideration: it was noted that there were some domains of skills in health promotion of Community Health Agents among adolescents, but there is a need for continuing education regarding the approach, for these professionals, in relation to knowledge and skills of health promotion.